Video polysomnographic findings in non‐rapid eye movement parasomnia. (8th October 2018) - Drakatos, Panagis; Marples, Lucy; Muza, Rexford; Higgins, Sean; Nesbitt, Alexander; Dongol, Eptehal M.; Macavei, Raluca; Gnoni, Valentina; Perez Carbonell, Laura; Duncan, Iain; Birdseye, Adam; Dastagir, Sakina; et al.
Abstract: Although video polysomnography (vPSG) is not routinely recommended for the evaluation of typical cases of non‐rapid eye movement (NREM) parasomnias, it can aid diagnosis of unusual cases, other sleep disorders and complicated cases with REM behaviour disorder (RBD), and in differentiating parasomnias from epilepsy. In this study, we aimed to assess vPSG findings in consecutive patients with a clinical diagnosis of NREM‐parasomnia covering the whole phenotypic spectrum. Five hundred and twelve patients with a final diagnosis of NREM parasomnia who had undergone vPSG were retrospectively identified. vPSGs were analysed for features of NREM parasomnia and for the presence of other sleep disorders. Two hundred and six (40.0%) patients were clinically diagnosed with sleepwalking, 72 (14.1%) with sleep terrors, 39 (7.6%) with confusional arousals, 15 (2.9%) with sexsomnia, seven (1.4%) with sleep‐related eating disorder, 122 (23.8%) with mixed phenotype, and 51 (10.0%) with parasomnia overlap disorder (POD). The vPSG supported the diagnosis of NREM parasomnia in 64.4% of the patients and of POD in 98%. In 28.9% of the patients, obstructive sleep apnea (OSA) or/and periodic limb movements during sleep (PLMS) were identified, most commonly in older, male, sleepy and obese patients. vPSG has a high diagnostic yield in patients with NREM parasomnia and should be routinely performed when there is diagnostic doubt, or in patients where there is a suspicion of OSA and PLMS.